(3GdfXQjGJ GdGbJUGOjI ddefTCIs - (3egOjO(B, (3aGWeI GdRgQGAs ((3GdLRGFQs (3OGQ GdHGMK ddWHGYI hGdfTQ hGdJhRjYs, 2023)
(3jgOa gPG GdcJGH Edi JSdjW GdVhA Ydi ehVhY GdfXQjGJ GdEbJUGOjI GdMOjKI HTcdg GdTGed, hYdi GdfXQjGJ GdEbJUGOjI ddefTCI aj JfXje hJSjjQ efXeGJ GdCYeGd, dJMbjb MGdI ef GdfLGM hGdJahb hGdGfJTGQ hGdJj JDOj HGdXQhQI Edi JYRjR bOQGJgG GdJfGaSjI hMUO GdMUI GdShbjI GdefThOI hGdGSJeQGQ HbhI(B. (3eeG jOd Ydi CgejI ehVhY fXQjI GdefTC Ydi GdeSJhjjf GdfXQj hGdJWHjbj(B. (3hdcj fHQR CgejI GdehVhY fMGhd Gdhbha Ydi Cge Jdc GdfXQjGJ hYdi Cge QhGOgG eQhQG HCge GdeTGcd GdJj YGdLJgG GdfXQjGJ hGdJj JUH aj eUdMI GdefTBJ(B.s
Keywords: (3GdEbJUGOs; (3GdfXQjGJ GdEbJUGOjIs